SVM-based algorithm for recognition of QRS complexes in electrocardiogram - Mehta, S.S.; Lingayat, N.S. (Ingénierie et recherche biomédicale, 2008)
Among all electrocardiogram (ECG) components, the QRS complex is the most significant feature. This paper presents a new algorithm for recognition of QRS complexes in the electrocardiogram (ECG) based on support vector machine (SVM). Digital filtering techniques are used to remove power line interference and baseline wander in the ECG signal. SVM is used as a classifier to delineate QRS and non-QRS regions. Algorithm performance was evaluated against the standard CSE ECG database. The results indicated that the algorithm achieved 99.3% of the detection rate. The percentage of false positive and false negative was 12.4 and 0.7% respectively. It could function reliably even under the condition of poor signal quality of the ECG signal. Parmi tous les composants ECG, le QRS complex est la fonctionnalité la plus importante. Cet article présente un nouvel algorithme pour reconnaître les QRS complex dans l’électrocardiogramme (ECG) sur la base du support vector machine (SVM). Des techniques digitales de filtrage sont utilisées pour éliminer les interférences entre les lignes électriques et la variation de la base line au niveau du signal de l’ECG. Le SVM est utilisé comme un classificateur pour délimiter les régions QRS et non-QRS. La performance de l’algorithme a été évaluée par rapport à la base de données CSE ECG. Les résultats indiquent que l’algorithme atteint 99,3 % du taux de détection. Le pourcentage de faux positifs et faux négatifs était respectivement de 12,4 et 0,7 %. Il peut fonctionner de façon fiable même si la qualité du signal de l’ECG est assez pauvre.